Investigations on Bi Doped Cu2Se Prepared by Solid State Reaction Technique for Thermoelectric Applications - Chaithanya Purushottam Bhat; Anusha; Aninamol Ani; U. Deepika Shanubhogue; P. Poornesh; Ashok Rao; Saikat Chattopadhyay (Energies, 2023)
The influence of Bi doping on the structural and thermoelectric properties of Cu2Se is presented in this work. Cu2−xBixSe (x = 0.00, 0.004, 0.008, 0.012) samples were prepared using conventional solid-state reaction techniques. According to room temperature XRD results, Cu2−xBixSe samples have a monoclinic crystal structure. Doping Bi to the Cu site acts as a donor, lowering the hole concentration, except for the sample with x = 0.004. The resistivity of the Cu2−xBixSe sample increases with an increase in Bi content. Seebeck coefficient data confirm that the holes are the charge carriers in Cu2−xBixSe samples. At 700 K, the Cu1.988Bi0.012Se sample has the highest power factor of 1474 μWm−1K−2, showing great potential in developing high-performance Cu2Se based thermoelectric materials.